A rare case of asymptomatic solitary cutaneous mastocytoma in a child - Jain, Sonam; Nanda, Saumya; Shastri, Malvika; Sethi, Divya (Indian Journal of Case Reports, 2021)
Mastocytosis is a rare group of disorders occurring when mast cells diffusely infiltrate the skin or internal organs. It has two forms: Cutaneous and systemic mastocytosis. We present a case of a 12-year-old male child presenting with a reddish-brown cutaneous nodule on the anterior chest wall for 1 month. No other similar lesions were noted elsewhere. Routine hematological and radiological investigations did not reveal any abnormality. The lesion was excised, and a diagnosis of solitary cutaneous mastocytoma was made based on the clinical, histopathological, and immunohistochemical features. This case highlights the importance of diagnosing this rare tumor which can present as an asymptomatic cutaneous lesion in a young child.